L233P mutation in the bovine leukemia virus Tax protein depresses endothelial cell recruitment and tumorigenesis in athymic nude mice - Mori, Hiroshi; Tomiyasu, Takafumi; Nishiyama, Kanako; Matsumoto, Maiko; Osawa, Yoshiaki; Okazaki, Katsunori (Archives of virology, 2019)
Bovine leukemia virus (BLV) can be divided into two categories based on the amino acid at position 233 in the Tax protein, which probably plays a crucial role in leukemogenesis. We show here that a rat fibroblast cell line stably expressing L233-Tax formed significantly larger tumors than P233-Tax-expressing cells in a murine xenograft study. Although the microvessel density was comparable in both tumors, visible blood vessel invasion was observed only on tumors from L233-Tax-expressing cells. Endothelial cell tube formation assays using human umbilical vein endothelial cells showed no significant difference in angiogenic activity between conditioned medium from L233- and P233-Tax-expressing cells, whereas in vitro chemotaxis assays revealed that only L233-Tax-expressing cells produced a chemoattractant for endothelial cells. Since pathological neovascularization can occur from the recruitment of endothelial progenitor cells, these results suggest that L233-Tax-expressing cells recruit murine endothelial progenitor cells and promote neovascularization to support tumor growth. BLV-infected lymphoma cells may also recruit bovine endothelial progenitor cells to promote neovascularization. The findings of this study are consistent with our previous observation that BLV carrying P233-Tax has a significantly longer incubation period for developing tumors than the virus carrying L233-Tax and provide insight into the function of Tax in leukemogenesis by BLV.